1820 Terr. of Mich. Laws 207, An Act For The Punishment Of Crimes, §§ 29-31. - (:unkn) unknown (General Publisher, 1820)
Sect. 30. And be it further enacted, That if any person shall unlawfully and maliciously assault another, with any offensive weapon or instrument, or by menaces, or in and by other forcible and violent manner and means, demand of another any money, or personal goods and chattels, with intent to rob him or her, or shall by day, willfully[1] and maliciously break and enter any dwelling house, shop, ware house, store house, mill, barn, stable, out house or other building whatever, with intent to kill, rob, steal, or commit a rape, mayhem or battery, then and in every such case, the person so offending, and each of the counsellors, procurers, aiders and abettors of the person so offending, shall, on being thereof convicted, be punished by fine not exceeding five hundred dollars, or solitary imprisonment, at hard labor, not exceeding ten years, or both, at the discretion of the court.
--Sect. 31. And be it further enacted, That if any person shall willfully[2] and maliciously enter, either by day or by night, without breaking the same, any church, meeting house, or place of worship, or any dwelling house, shop, ware house, store house, mill, barn, stable, out house or other building whatsoever, with intent to kill, rob, steal, or to commit a rape, mayhem or battery, then and in every such case, the person so offending, and each of the counsellors, procurers, aiders, and abettors of such offender, shall, on conviction, be punished by fine not exceeding three hundred dollars, or by solitary imprisonment, at hard labor, not exceeding five years, or both, at the discretion of the court.”
--
Keywords: CARRY - INTENT TO COMMIT CRIME